Structure and function of the Saccharomyces cerevisiae CDC2 gene encoding the large subunit of DNA polymerase III. - Boulet, A (1989)
Saccharomyces cerevisiae cdc2 mutants arrest in the S-phase of the cell cycle when grown at the non-permissive temperature, implicating this gene product as essential for DNA synthesis. The CDC2 gene has been cloned from a yeast genomic library in vector YEp13 by complementation of a cdc2 mutation. An open reading frame coding for a 1093 amino acid long protein with a calculated mol. wt of 124,518 was determined from the sequence. This putative protein shows significant homology with a class of eukaryotic DNA polymerases exemplified by human DNA polymerase alpha and herpes simplex virus DNA polymerase. Fractionation of extracts from cdc2 strains showed that these mutants lacked both the polymerase and proofreading 3'-5' exonuclease activity of DNA polymerase III, the yeast analog of mammalian DNA polymerase delta. These studies indicate that DNA polymerase III is an essential component of the DNA replication machinery.